Comparing the Relative Interfacial Affinity of Soft Colloids With Different Crosslinking Densities in Pickering Emulsions - Kwok, Man-hin; Ngai, To (Frontiers in Chemistry, 2018)
Pickering emulsions prepared by various kinds of soft colloids such as the poly(N-isopropylacrylamide) (PNIPAM)-based microgels, have been studied for decades in order to fabricate stimuli-responsive emulsions. It has been generally viewed that the interfacial properties of the microgel monolayers and the emulsion stability are dominated by the softness or deformability of the microgel particles. However, there is still no convenient way to characterize the adsorption/desorption energy of the microgels at the interface although this is an essential topic for microgel-stabilized emulsions. This paper presents a novel method for directly comparing the relative interfacial affinity of microgel particles with comparable size but different crosslinking densities, therefore, different softness at the oil/water interface. Typical micron-sized PNIPAM-based microgels were synthesized and used in this study. With advanced fluorescent labeling techniques, we are capable of distinguishing different kinds of microgels in a Pickering emulsion. During vigorous agitation, particles with higher adsorption energy are more likely to be found at the oil/water interface instead of the loosely adsorbed counterparts. By counting the ratio of interfacial area occupied by two microgels, the interfacial affinity of them can be compared. It is found that interfacial affinity of microgels is not only dependent on the softness but also strongly correlated with the core-shell morphology of the microgels, especially the outmost collapsed polymer layer at the interface. This result is consistent with the interfacial morphology model proposed by other researchers. The understanding of the stabilization of such Pickering emulsions can help us to design and develop responsive Pickering emulsions with better controlled stability.